Indemnity Payments and Gold Movements - Robertson, D. H. (Quarterly Journal of Economics, 1939)
Journal Article Indemnity Payments and Gold Movements Get access D. H. Robertson D. H. Robertson Trinity College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 53, Issue 2, February 1939, Pages 312–314, https://doi.org/10.2307/1882893 Published: 01 February 1939